Wake Forest students on the quad - Grigg Studio (Z. Smith Reynolds Library, 1956)
Photo appeared in Wake Forest Magazine, August 1956, p. 9.
Students walking on quad, photographed from upper window of Wait Chapel.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth